Tipologi Abreviasi Pada Lembar Evaluasi Diri Borang Akreditasi - Anita Angraini Lubis (Jurnal Hata Poda, 2023)
This study aims to describe the form, function, process, and typology of abbreviations in self-evaluation reports on study program accreditation forms. The research method used is descriptive qualitative. The data sources for this research are various abbreviations used in self-evaluation reports for accreditation forms in study programs. Analysis of the research data using the flow model of analysis. The results showed (1) the form of abbreviation includes abbreviations, acronyms, contractions, fragments, and letter symbols, (2) the function of abbreviations includes (a) to save on the use of long words by retaining the letters or syllables of words or phrases its formation, (b) bringing out language variations in written works, and (c) so that writing is more practical. (3) The process of forming abbreviations includes retaining the first letter, retaining the first letter and removing conjunctions, retaining the first syllable, and summarizing the lexemes of the basic forms. Abbreviation typology in Indonesian-language newspapers consists of 5 types including (1) maintenance of the first letter, 2) maintenance of the first letter by omitting the assignment word, 3) maintenance of the first letter and fulfillment of phonotic rules, 4) maintenance of syllables and fulfillment of phonotic rules, 5) syllable maintenance, omission of the word assignment, and fulfillment of phonotactic rules, Keywords: Self-Evaluation Sheet, Accreditation Form, Abbreviation Typology